PERAN CUSTOMER ENGAGEMENT MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP BRAND AWARENESS PADA E-LEARNING AKU PINTAR - Gandhi, Chatarina Puspita; Ekawati, Ni Wayan; Widagda K, I Gst Ngurah Jaya Agung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
Technology in the education sector have implications for changing learning styles that previously focused on face-to-face learning models, now carried out with e-learning models. Aku Pintar is the e-learning choice alternative for students, but Aku Pintar's brand awareness is still not as big as its competitors. This study aims to examine and explain the role of customer engagement in mediating the influence of social media marketing on Aku Pintar e-learning brand awareness. Data were collected using an online questionnaire to 175 respondents in Jakarta. This study used a purposive sampling method. The data analysis technique in this study used Path Analysis, the Variance Accounted For Test (VAF), and the Sobel Test. The results of this study indicate that social media marketing has a positive and significant effect on brand awareness and customer engagement, customer engagement has a positive and significant effect on brand awareness, and customer engagement is expressed as a partial mediation in the relationship between social media marketing and brand awareness in the Aku Pintar e-learning. The implication of this research for Aku Pintar is information for Aku Pintar to evaluate indicators with values below the average so they can develop a more effective social media marketing strategy.